THE STRATEGY OF THE STATE SUPPORT OF SPHERE OF SERVICES - N. V. Rozhkova (Финансы: теория и практика)
The task of governments to create the necessary conditions for the successful functioning of enterprises of different industries is one of the primary. The service sector is important for the population, covering sectors such as residential, tourist, psychological, educational and legal services in whole in the penitentiary system in particular. This creates favorable conditions for the development of society and therefore the economy as a whole. In services, it is important to take into account the peculiarities of the functioning of the industry, why, and will depend on the effectiveness of measures by the state. The article presents the problems hindering the development of this industry and defined measures of state support on the example of sphere of tourist services.